Strategi Pengembangan Pembelajaran Pendidikan Agama Islam Berbasis Teknologi Informasi di SMP UNISMUH Makassar - Wahyu Hidayat; Muhammad Ali Bakri; Sulaeman (Advances In Education Journal, 2025)
This study aims to: (1) analyze the application of information technology in Islamic Education learning at SMP Unismuh Makassar; (2) explore the challenges faced in developing IT-based Islamic Education; and (3) examine the strategies applied to improve the use of technology in the learning process. The research employed a descriptive qualitative approach. Data were collected through observation, interviews, and documentation, and then analyzed using data reduction, data display, and conclusion drawing.The findings show that the use of information technology in Islamic Education learning has been implemented quite well. Teachers have utilized various digital media such as PowerPoint, YouTube, and interactive platforms (Kahoot, Quizizz) to make lessons more engaging and to increase student participation. However, several challenges remain, including technical problems (such as power outages and unstable internet connections), school policies limiting the use of students’ personal devices, and differences in students’ digital literacy. To address these challenges, the school and teachers have provided digital materials that can be accessed without personal devices and developed interactive and flexible teaching approaches. These strategies are intended to ensure that technology meaningfully supports students’ understanding of the subject matter.